Предмет: Алгебра,
автор: шаьалцщ03ц20033в
15 БАЛЛОВ
ОЧЕНЬ СРОЧНО
РЕШИТЕ С ПОДРОБНЫМ РЕШЕНИЕМ
Приложения:
Ответы
Автор ответа:
0
0 0 0
∫(3x^2+5x-1)dx=(3* (x^3 /3) +5*(x^2 /2) -x )| =(x^3 +2,5 x^2 -x) | =0^3
-1 -1 -1
+2,,5*0^2- 0 -( (-1)^3 +2,5*(-1)^2 +1)=1-2,5-1=-2,5
0 -( (-1)^3 +2,5*(-1)^2-1)=1-2,5+1=-0,5
∫(3x^2+5x-1)dx=(3* (x^3 /3) +5*(x^2 /2) -x )| =(x^3 +2,5 x^2 -x) | =0^3
-1 -1 -1
+2,,5*0^2- 0 -( (-1)^3 +2,5*(-1)^2 +1)=1-2,5-1=-2,5
0 -( (-1)^3 +2,5*(-1)^2-1)=1-2,5+1=-0,5
Похожие вопросы
Предмет: Другие предметы,
автор: Parniksam
Предмет: История,
автор: Blianblyan
Предмет: Українська мова,
автор: malnastya392
Предмет: Математика,
автор: pon4ik14
Предмет: Алгебра,
автор: ksusha1521